Zimbabwe’s Curriculum Framework As An Image of the Presidential Commission of Inquiry into Education Recommendations - Chikuvadze, Pinias; Mutseekwa, C; Zuva, Joseph; Maguya, Susan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Zimbabwe needs to transform its curriculum to one that meets local and global relevance. Against this background, this paper's primary concern was to understand the link between the curriculum framework (2015-2022) and some of the recommendations advanced by the Presidential Commission of Inquiry into Education (1999). A systematic review approach guided the analysis and discussion of the source data. This analysis counts on key bibliographic databases: Science Direct, Scopus, Web of Science, and Google Scholar through a huge quantity of research papers. This qualitative content analysis was conducted to conceptualize the Presidential Commission of Inquiry into Education report’s recommendations on high school education, as the pillar of the curriculum framework (2015-2022). In addition, continuous assessment was discussed as a pedagogical issue in the context of the curriculum framework (2015-2022). It can be concluded that the existing link between the Presidential Commission on Education and Training recommendations and the curriculum framework (2015-2022) has created the basis for the inclusion of continuous assessment in learning activities in high schools. Based on the conclusions the researchers recommended the need to employ multi-modalities to improve the efficiency and effectiveness of the new approach in learning activities in high schools.